Web of Things Gateway - a Performance Evaluation - Andrade Jr., Nailton Vieira de; Almeida, Jeferson Lima de; Costa, Ramon Dias; Andrade, Leandro José Silva; Pinto, Geroge Pacheco; Prazeres, Cássio Vinicius Serafim (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
The Web of Things is a proposal to make physical and connected devices available to be used as resources in the development of Web applications through the Web protocols and standards. On the one hand, the current Web has virtual content, which is accessed by client applications that are hosted on Web servers, but on the other hand, the physical devices are real objects that are geographically distributed and have several different ways of communication. As a result of these two before-mentioned characteristics, the physical devices would demand a larger number of Web servers. In this context, this work proposes that devices with limited memory capacity and processing power can be used as Web of Things gateways through Web protocols. Then, performance evaluation of such limited device is presented in this paper with two evaluation objectives: to evaluate the feasibility of a limited device as a Web of Things gateway; to establish the capacity of the gateway in management the access to the physical devices.